2009
DOI: 10.1002/mus.21526
|View full text |Cite
|
Sign up to set email alerts
|

Ros‐mediated activation of NF‐κB and Foxo during muscle disuse

Abstract: We examined reactive oxygen species as upstream activators of NF-κB and Foxo in skeletal muscle during disuse atrophy. Catalase, an enzyme that degrades H 2 O 2 , was overexpressed in soleus muscles via plasmid injection prior to seven days of hind limb immobilization. The increased catalase activity abolished immobilization-induced transactivation of both NF-κB and Foxo, and it attenuated the loss of muscle mass. Thus, H 2 O 2 may be an important initiator of these signaling pathways which lead to muscle atro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(89 citation statements)
references
References 27 publications
1
87
0
1
Order By: Relevance
“…Interestingly, this effect was associated with a reduction of FOXO and NF-κB activation. These results have been confirmed by using antioxidant agents such as EUK-134 (SOD and catalase mimetic) [71] and SS-31 (mitochondria-targeted antioxidant) [54,121]. The inhibition of mitochondrial ROS production prevented soleus atrophy and UPS/autophagy activation induced by casting [54], whereas EUK-134 limited skeletal muscle atrophy and FOXO3a activation induced by hindlimb unloading [71].…”
Section: Evidence For a Role Of Rons In Immobilization-induced Skeletmentioning
confidence: 78%
See 1 more Smart Citation
“…Interestingly, this effect was associated with a reduction of FOXO and NF-κB activation. These results have been confirmed by using antioxidant agents such as EUK-134 (SOD and catalase mimetic) [71] and SS-31 (mitochondria-targeted antioxidant) [54,121]. The inhibition of mitochondrial ROS production prevented soleus atrophy and UPS/autophagy activation induced by casting [54], whereas EUK-134 limited skeletal muscle atrophy and FOXO3a activation induced by hindlimb unloading [71].…”
Section: Evidence For a Role Of Rons In Immobilization-induced Skeletmentioning
confidence: 78%
“…In skeletal muscle of rats, catalase overexpression prevented immobilization-induced skeletal muscle atrophy [121]. Interestingly, this effect was associated with a reduction of FOXO and NF-κB activation.…”
Section: Evidence For a Role Of Rons In Immobilization-induced Skeletmentioning
confidence: 91%
“…We next analyzed how Actβ is induced in mitochondria-perturbed muscle. Perturbation of the mitochondrial complex I has been shown to robustly increase intracellular production of ROS (reactive oxygen species) signaling molecules and to activate various downstream kinase/transcriptional factor signaling pathways (16)(17)(18). We have also shown that complex I perturbation in the larval muscle triggers ROS production and activates transcription factors like FoxO, JNK, and NF-κB/Rel (8).…”
Section: The Ros/nf-κb Cascade Autonomously Regulates Actβ Expression Inmentioning
confidence: 87%
“…During disuse, mitochondrial reactive oxygen species (ROS) production leads to mitochondrial dysfunction and muscle atrophy (71). ROS can regulate NF-B and FoxO signaling, thereby leading to the activation of atrogenes (18). Decreased sympathetic stimulation of muscle may also play a role in inactivity-related muscle wasting.…”
Section: Tgf-␤mentioning
confidence: 99%